Finite Element Modeling of a Reinforced Concrete Column Strengthened with Steel Jacket - Hamza Mahdi Salman; Mohannad Husain Al-Sherrawi (Civil Engineering Journal, 2018)
The reinforced concrete column is designed to have a nominal axial resistance. Under different conditions like errors in design, and changing the use of the building from residential to public or storage (extra live loads), the reinforced concrete column will not be able to sustain the desired applied load, and the strengthening is required. This paper presents a finite element model to simulate and investigate the behavior of adding steel jacket to a preloaded and non-damaged reinforced concrete column. Depending on the loading state of the non-strengthened reinforced concrete column and the purpose of adding the steel jacket, two possible cases have been studied. In the first case, which is suitable to investigate the reinforced concrete column with design errors, the steel jacket has been added to the unloaded reinforced concrete column; while the second case is suitable for adding steel jacket to the pre-loaded non-damaged reinforced concrete column. The finite element model was carried out using the ABAQUS/standard v. 6.13 software. The results obtained by the proposed finite element model showed fairly good agreement with the existing experimental and analytical results.